2006
DOI: 10.1088/0957-4484/17/5/039
|View full text |Cite
|
Sign up to set email alerts
|

Uniform and selective CVD growth of carbon nanotubes and nanofibres on arbitrarily microstructured silicon surfaces

Abstract: Carbon nanotubes (CNTs) and nanofibres (CNFs) are grown on bulk-micromachined silicon surfaces by thermal and plasma-enhanced chemical vapour deposition (PECVD), with catalyst deposition by electron beam evaporation or from a colloidal solution of cobalt nanoparticles. Growth on the peaked topography of plasma-etched silicon 'micrograss' supports, as well as on sidewalls of vertical structures fabricated by deep-reactive ion etching demonstrates the performance of thermal CVD and PECVD in limiting cases of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…When developing vertically aligned CNTs grown by chemical vapor deposition (CVD), the growth of the CNTs depends on the catalyst film thickness, substrate type, ratio of feed gas, temperature, and gas pressure. Several studies have been carried out to grow multiwalled carbon nanotubes (MWCNTs) from CVD or plasma-enhanced CVD using single-metal Co, Fe, and Ni as catalysts on various substrates [6][7][8]. To further improve the density of MWCNTs, plasma pretreatment is performed on these typical catalyst particles to enhance catalyst formation and stability onto the substrate [9].…”
Section: Introductionmentioning
confidence: 99%
“…When developing vertically aligned CNTs grown by chemical vapor deposition (CVD), the growth of the CNTs depends on the catalyst film thickness, substrate type, ratio of feed gas, temperature, and gas pressure. Several studies have been carried out to grow multiwalled carbon nanotubes (MWCNTs) from CVD or plasma-enhanced CVD using single-metal Co, Fe, and Ni as catalysts on various substrates [6][7][8]. To further improve the density of MWCNTs, plasma pretreatment is performed on these typical catalyst particles to enhance catalyst formation and stability onto the substrate [9].…”
Section: Introductionmentioning
confidence: 99%
“…The experiment results revealed that most of the CNTs deposited by plasma-enhanced CVD and by thermal CVD generally grow in the tip-growth [ 12 - 21 ] and base-growth [ 22 - 29 ] modes, respectively. The results indicated the adhesion force between catalyst and substrate to be the main factor in CNT growth modes [ 11 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…About CNT growth modes, the adhesion force at catalyst/substrate interface was first proposed by Bower’s group as one of the most important factors [ 11 ]. Although tip-growth CNTs are the most common CNTs grown through plasma-enhanced chemical vapor deposition (CVD) [ 12 - 21 ], many investigators are searching for ways to grow base-growth CNTs by increasing adhesion force between the catalyst and substrate. Some proposed methods include using a metal catalyst to form metal-silicide with Si substrate, implanting catalyst ions into the substrate and increasing the decomposition temperature of the catalyst precursor [ 11 , 51 - 54 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topography-driven effects on particle size, and therefore on catalytic activity, will vary widely among different catalyst and CVD methods. Further, we demonstrate growth of aligned Carbon Nanofibres (CNFs) by plasma-enhanced CVD on silicon 'micrograss', using a colloidal solution of Co nanoparticles as the catalyst (Hart et al, 2006c). We expect that his process can be extended to grow a wide variety of nanostructures on microstructures having arbitrary three-dimensional topography, extending the fabrication capability for hierarchically microstructured and nanostructured substrates, for applications such as super-hydrophobic surfaces and cell growth.…”
Section: Conformal Cnt Films Grown Directly On Bulk Microstructuresmentioning
confidence: 99%